2018
DOI: 10.32473/edis-fa208-2018
|View full text |Cite
|
Sign up to set email alerts
|

Production and Performance of Triploid Oysters for Aquaculture

Abstract: This 9-page fact sheet written by Huiping Yang, Natalie Simon, and Leslie Sturmer and published by the Program in Fisheries and Aquatic Sciences of the UF/IFAS School of Forest Resources and Conservation focused on basic aspects of triploid oyster aquaculture, including the general oyster aquaculture industry, the approaches for triploid induction, performance of triploids, and correlated ploidy determination to convey basic knowledge of triploid oyster aquaculture to the oyster industry and the general public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…So far, two types of polyploid oysters, triploids and tetraploids, were developed. Tetraploids oysters are produced for further crossing diploid oysters, resulting in the production of triploids oysters (Yang et al 2018).…”
Section: Polyploidymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, two types of polyploid oysters, triploids and tetraploids, were developed. Tetraploids oysters are produced for further crossing diploid oysters, resulting in the production of triploids oysters (Yang et al 2018).…”
Section: Polyploidymentioning
confidence: 99%
“…Tetraploids oysters are produced for further crossing diploid oysters, resulting in the production of triploids oysters (Yang et al . 2018).…”
Section: Geneticsmentioning
confidence: 99%
“…Triploid oysters, for example, often exhibit characteristics such as rapid growth, superior meat quality and year-round harvestability because they have three sets of chromosomes [4]. Currently, triploid oyster aquaculture has become an important part of the global industry [5]. In the case of H. discus hannai , research on triploids dates to the late 1990s when studies demonstrated that triploids had a growth advantage over their diploid counterparts [6‒9].…”
Section: Introductionmentioning
confidence: 99%